Pengembangan Sistem E-Pembelajaran Siswa Berbasis Web (Studi Kasus: SMAN 1 Bululawang) - Shafitri Noviagsani Putri; Adam Hendra Brata; Herman Tolle (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The absence of mid-term test and final exam score reporting system at SMAN 1 Bululawang was causing the students to be unaware of the score they have been obtained. Aside from the solution of the existing problems, E-Pembelajaran system here functioned as the form of teaching and learning activities as well. The system of E-Pembelajaran also provides a feature named plagiarism checking for the assignments as well as quizzes which form is descriptive or essay. The feature of plagiarism checking is being developed using cosine similarity method. The development of this system is conducted using Software Development Life Cycle (SDLC) method and waterfall modeling. Requirement analysis done in this system is resulting in 4 actors, 46 functional requirements, and 1 non-functional requirement. This research used blackbox and whitebox test method with unit testing strategies, integration testing, and validation testing. The results of the tests conducted on those unit testing from 3 functional requirement tests produce valid values,, then on the integration test of 1 functional requirement tests valid values, and validation test which yields 100% valid from all functional requirement indicates that the system is in accordance with the requirement specification. Non-functional test conducted is the compatibility test which expected the system to be able to run in different user environments, such as in google chrome, mozila firefox, internet explorer, microsoft edge, opera dan perangkat mobile.